2018
DOI: 10.1186/s40503-018-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric real-exchange-rate effects on capital accumulation: evidence from non-linear ARDL models for Mexico

Abstract: According to recent development studies, a depreciated real-exchange-rate (RER) level can increase the rate of economic growth, particularly so in developing countries and in the medium run. But although many studies have supported this proposition, others have questioned it: a depreciated RER may facilitate but not ensure faster growth; or appreciations may hurt growth while depreciations play a more neutral role; or both appreciations and depreciations relative to an equilibrium level may in fact decelerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…11. Other studies have found positive effects of RER undervaluation specifically on manufacturing investment (for example, Ibarra (2018) for Mexico and Marconi et al (2022) for Brazil), and one study has found a positive effect on manufacturing output (Nalín/Moreno-Brid 2022). These results suggest that RER depreciation can influence structural change in favor of the manufacturing sector, which can contribute to long-run growth.…”
Section: The Evidence On Growthmentioning
confidence: 90%
See 1 more Smart Citation
“…11. Other studies have found positive effects of RER undervaluation specifically on manufacturing investment (for example, Ibarra (2018) for Mexico and Marconi et al (2022) for Brazil), and one study has found a positive effect on manufacturing output (Nalín/Moreno-Brid 2022). These results suggest that RER depreciation can influence structural change in favor of the manufacturing sector, which can contribute to long-run growth.…”
Section: The Evidence On Growthmentioning
confidence: 90%
“…On the one hand, the marginal propensity to save out of profits is typically higher than out of profits for well-known reasons. On the other hand, raising profitability tends to encourage investment (and attracts foreign direct investment) in tradable goods industries (Ibarra 2018; Ibarra/Ros 2019), thereby expanding export capacity and potentially diminishing the need for imports (unless the exports are highly intensive in imported capital and intermediate goods).…”
Section: Concepts Complexities and Channelsmentioning
confidence: 99%